Análisis de incidencias del sistema contawin en la empresa I.V.M.A importer de la ciudad de Babahoyo - Posligua Ruiz, Gricelda Emperatriz (2021)
Technology today has become a fundamental pillar of Ecuadorian society, new technological tools facilitate our daily tasks. For companies, technology is essential due to the amount of information that is handled. Electronic invoicing accounting systems take more presence in the business sector, because they allow the information to be handled in an efficient way, thus controlling all the accounting entries, optimizing the processes that were previously carried out manually. The companies that implement electronic invoicing can create, transmit and digitally store their purchase and sale tax documents such as: invoices, due note, credit note, among others, for the Ecuadorian State it serves as a tool to reduce evasion of taxes.